Crystalline and Molecular Structure of Hydrated 2,6-Xylidinium Tetrachlorozincate(II) - W. Smirani; M. Rzaigui (E-Journal of Chemistry)
A new zinc complex compound of formula [2,6-(CH3)2-C6H3NH3]2ZnCl4. 2H2O has been prepared and characterized by X-ray crystallography, thermal analysis and IR spectroscopy. The complex crystallizes in the monoclinic space group P21/a with a minimal tetrahedral distortion of the ZnCl42- ion, a = 7.448(1) Å, b = 38.486(3) Å, c = 8.298(1) Å, β= 112.52(1) °, V = 2197.4(4) Å3 and Z = 4. The crystal structure was solved and refined to R = 0.047 with 3270 independent reflections. It can be described by inorganic layers of [ZnCl4.(H2O)2]2- parallel to (010) plane, between which the 2,6-xylidinium cations are located. The grouping is maintained by different types of interactions (electrostatic, H-bonds, Van der Walls and π-π stacking). A characterization of this compound by thermal analysis and IR spectroscopy are also reported.